(untitled) (Fiep Bulletin - online, 2011)
This study aims to investigate the PFRH of women from Curiaú community, Macapá-AP, The non-probabilistic intentional sample was composed by 14 volunteer women, aged between 21 to 47, divided in two groups G1(06), under 30 years old and G2 (08) over 30 years old. Anthropometric data regarding Height and Corporal Mass has been collected to determine the Body mass index (BMI), Hip and Waist Perimeter (RQC), in order to obtain the Hip and Waist Relation (RCQ), assessed according to criteria established by Nahas (2003).The tests used to assess superior members (elbow flexion) strength/resistance and flexibility (sit and reach) assessed according to Nieman (1999). Cardio respiratory Resistance (1609 meters walking tes) established by Cooper Institute of Aerobic Research mentioned by Nahas (2003). Results show that AFRS components, G2 is more frequent according to the criteria recommended for Strength/Resistance (62,5%) and Flexibility (87,5%), whereas G1 obtained (33,3%) for Stength/Resistance and (33,2%) for Flexibility. Meanage scores indicate that the sample did not reach rates recommended by the reference criteria for health in all of the components, highlighting the following meanage scores: Cardiovascular component (20,50 ± 9,33 and 20,34 ± 10,34 ml.kg.kg-1 for G1 and G2 respectively), body composition (IMC= 26,01 ± 3,52 and 26,39 ± 4,23 kgm2 for G1 and G2 respectively), Strength/Resistance (12,5 ±4,5 and 13,62 ± 3,29 for G1 and G2 respectively), Flexibility (29,58 ± 7,77 and 35,5 ± 6,5 cm). Results show incompatibility between AFRS aspects and reference criteria established by literature.